PENGARUH PARTISIPASI ANGGARAN, KEJELASAN SASARAN ANGGARAN, DAN KECUKUPAN ANGGARAN TERHADAP KINERJA MANAJERIAL (STUDY PADA SMKS DI KABUPATEN TANGERANG) - Retno Puji Astuti; Hadri Mulya (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2019)
The purpose of this study is to analyze the influence of participation in budgeting, budget objectives clarity, and budgetary adequacy toward managerial performance. The data used in this study is obtained from ideas or perceptions of teachers, principals and their staffs who filled and submitted the questionnaires to the researcher. The data was collected by a direct survey. The survey was conducted from April 2016 to June 2016. Of 120 questionnaires distributed to Private Vocational High School in Tangerang district, 100 (83.3%) questionnaires were responded and followed with analysis using SEM multivariate technique and PLS 3.0 software. The study found that participation in budgeting has a positive significant effect on managerial performance while the analysis of the budget objectives clarity shows that it does not influence any managerial performance. Similarly, budgetary adequacy brings positive influence yet insignificant toward managerial performance. Therefore, the school institution should promote budget participation in order to improve the managerial performance.